2020
DOI: 10.1371/journal.pone.0233523
|View full text |Cite
|
Sign up to set email alerts
|

The acute effects of cigarette smoke exposure on muscle fiber type dynamics in rats

Abstract: Reduced exercise capacity is common in people with chronic obstructive pulmonary diseases (COPD) and chronic smokers and is suggested to be related to skeletal muscle dysfunction. Previous studies using human muscle biopsies have shown fiber-type shifting in chronic smokers particularly those with COPD. These results, however, are confounded with aging effects because people with COPD tend to be older. In the present study, we implemented an acute 7-day cigarette smoke-exposed model using Sprague-Dawley rats t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Furthermore, the same study demonstrated that acutely treating healthy soleus muscles with cigarette smoke extract impaired mitochondrial respiration [ 16 ]. Additional work in rats reported a reduction in muscle citrate synthase activity, a marker of mitochondrial content, following only 7-days of cigarette smoke exposure [ 17 ]. Therefore, these studies demonstrate that active smoking acutely impairs muscle mitochondrial health, which can be recovered upon smoking cessation, suggesting that tobacco smoke contains chemicals that are toxic to muscle mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the same study demonstrated that acutely treating healthy soleus muscles with cigarette smoke extract impaired mitochondrial respiration [ 16 ]. Additional work in rats reported a reduction in muscle citrate synthase activity, a marker of mitochondrial content, following only 7-days of cigarette smoke exposure [ 17 ]. Therefore, these studies demonstrate that active smoking acutely impairs muscle mitochondrial health, which can be recovered upon smoking cessation, suggesting that tobacco smoke contains chemicals that are toxic to muscle mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…The extra-pulmonary changes inherent to CS could also reduce muscle endurance and strength, ultimately leading to diminished exercise capacity and regenerative response. 11 Curiously, the speed and time running did not differ significantly between mice nonsmokers and smokers, which could be partially explained by similar body weight between groups and substantial metabolic adjustments. Optimal body weight maintenance may compensate the skeletal muscle energy metabolism during exercise to maintain exercise capacity and tolerance.…”
Section: Discussionmentioning
confidence: 90%
“…The heterogeneity of fiber size in the present study is consistent with previous reports on human 33 and rodent skeletal muscle after CS exposure. 11 Such heterogeneous fiber size distribution is believed to be associated with the redistribution of muscle fiber types observed in CS exposure, shifting from type I oxidative muscle fibers to type II glycolytic muscle fibers. 11 A non-uniform atrophy response can be a considerable adaptation to the CS condition, generally related to physiological character.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations